2000
DOI: 10.1007/s11630-000-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Relative stability of boiling of FC-72 and HFE-7100 with applications to electronic device cooling

Abstract: This paper investigates the relative stability between nucleate and film boiling modes of FC-72 and HFE-7100, which have potential to electronic device cooling applications. Equilibrium heat flux, qc, which refers to as an index for measuring the relative stability of boiling, was obtained at a liquid subcooling of 0-20 K. Experimental results reveal that (1) qc increases with liquid subcooling; (2) although the FC-72 exhibits a higher critical heat flux (CHF) than does the HFE-7100, somewhat unexpectedly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Published literature has investigated the thermal properties of hydrofluoroethers (HFE), [C 3 F 7 OCH 3 ], and fluorinated ketone (FK), [C 2 F 5 C(O)CF(CF 3 ) 2 ], and reported that they have comparable heat transfer performance with a commercial perfluorocarbon, which is FC 72 [6, 7]. Hence, these two new coolants have attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…Published literature has investigated the thermal properties of hydrofluoroethers (HFE), [C 3 F 7 OCH 3 ], and fluorinated ketone (FK), [C 2 F 5 C(O)CF(CF 3 ) 2 ], and reported that they have comparable heat transfer performance with a commercial perfluorocarbon, which is FC 72 [6, 7]. Hence, these two new coolants have attracted attention.…”
Section: Introductionmentioning
confidence: 99%